2000
DOI: 10.1086/309079
|View full text |Cite
|
Sign up to set email alerts
|

Adding More Mysteries to the DA White Dwarf GD 394

Abstract: We present spectroscopic and timing analyses of the hot DA white dwarf GD 394 showing abundance inhomogeneities across its surface. Lick Hamilton echelle, International Ultraviolet Explorer (IUE), HST GHRS, and Hopkins Ultraviolet Telescope (HUT) spectra show dominant Si III and Si IV features, while Extreme Ultraviolet Explorer (EUV E) spectra show evidence of a host of trace element opacities. We report the detection of Si III j4552 triplet with a measured radial velocity of 27 km s~1 in agreement with far u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(85 citation statements)
references
References 65 publications
7
77
1
Order By: Relevance
“…The origin of the metals has been intensively debated in the past (Shipman et al 1995;Bannister et al 2003;Barstow et al 2003;Dickinson et al 2012a,b), but it is very likely that it is, at least in part, also related to planetary debris (Barstow et al 2014). One particularly promising candidate of a hot white dwarf accreting planetary debris at a high rate is the extremely metal-polluted GD394 (≈40 000 K, Barstow et al 1996;Dupuis et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The origin of the metals has been intensively debated in the past (Shipman et al 1995;Bannister et al 2003;Barstow et al 2003;Dickinson et al 2012a,b), but it is very likely that it is, at least in part, also related to planetary debris (Barstow et al 2014). One particularly promising candidate of a hot white dwarf accreting planetary debris at a high rate is the extremely metal-polluted GD394 (≈40 000 K, Barstow et al 1996;Dupuis et al 2000).…”
Section: Resultsmentioning
confidence: 99%
“…The Si abundance by number is (Si/H)∼10 −5 . Dupuis et al (2000) suggest that the 1.15 day period variability seen in the EUVE light curve of GD 394 is due to inhomogeneous abundance distribution of metals over the surface of the star. In their model, an almost circular spot with a higher heavy element abundance reduces the EUV emission over the spot region, causing 25% dips in brightness.…”
Section: Not a Disintegrating Planetmentioning
confidence: 89%
“…GD 394 presents an unusual case where Dupuis et al (2000) detect 25% amplitude variations in the extreme ultraviolet with a period of 1.15 days, but there is no evidence of a magnetic field down to a limit of 12 kG. Dupuis et al (2000) interpret the observed photometric variations as evidence of surface abundance inhomogeneities.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations